2021
DOI: 10.1093/eurheartj/ehab777
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular and kidney outcomes with finerenone in patients with type 2 diabetes and chronic kidney disease: the FIDELITY pooled analysis

Abstract: Aims The complementary studies FIDELIO-DKD and FIGARO-DKD in patients with type 2 diabetes and chronic kidney disease (CKD) examined cardiovascular and kidney outcomes in different, overlapping stages of CKD. The purpose of the FIDELITY analysis was to perform an individual patient-level prespecified pooled efficacy and safety analysis across a broad spectrum of CKD to provide more robust estimates of safety and efficacy of finerenone compared with placebo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
462
0
63

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 581 publications
(534 citation statements)
references
References 30 publications
9
462
0
63
Order By: Relevance
“…Indeed, MRA such as eplerenone and spironolactone reduce the eGFR in the acute phase; however, they also exert a nephroprotective effect on the long-run [ 74 ]. This has also been demonstrated for finerenone [ 75 , 76 , 77 , 78 ].…”
Section: Other Examplesmentioning
confidence: 57%
“…Indeed, MRA such as eplerenone and spironolactone reduce the eGFR in the acute phase; however, they also exert a nephroprotective effect on the long-run [ 74 ]. This has also been demonstrated for finerenone [ 75 , 76 , 77 , 78 ].…”
Section: Other Examplesmentioning
confidence: 57%
“…The direct antifibrotic properties of finerenone resulted in reduced myofibroblast and collagen deposition accompanied by a decrease in kidney plasminogen activator inhibitor (PAI)-1 and naked cuticle 2 (NKD2) expression in mouse models of progressive kidney fibrosis (Droebner et al, 2021). Our data showing that the relative risk of a sustained ≥40% decrease in the eGFR was reduced by 15%, ESKD by 20%, and FIDELITY analysis showed the relative risk of a sustained ≥57% decrease in the eGFR was reduced by 30% (Agarwal et al, 2021a). These results indicate that finerenone may have long-term renal benefits for CKD patients.…”
Section: Discussionmentioning
confidence: 70%
“…However, Randomized Aldactone Evaluation Study (RALES) cautions us about what also might come following the publication of impactful results from controlled trials (Moura-Neto and Ronco, 2021). Therefore, routine potassium monitoring and hyperkalemia management strategies [finerenone treatment interruption and dose reduction or adding other therapies (such as diuretics or potassium binders)] are essential, which will minimize the impact of hyperkalemia and enable sustained clinical use of finerenone (Clase et al, 2020;Agarwal et al, 2021a;Epstein et al, 2021;Moura-Neto and Ronco, 2021). Notably, AEs are not all related to the trial regimen, although our meta-analysis showed a comparable incidence of AEs between the finerenone and placebo groups.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…For this pooled analysis population (n = 13,026) with median follow up of 3 years, there was a 14% decrease in the CV outcome and a 23% decrease in a composite kidney disease outcome (time to kidney failure, ≥57% sustained decline in eGFR or kidney related death). 8 As a result of these clinical trials, finerenone received United States Food and Drug Administration (US FDA) approval for reducing CKD progression, CV events, and HF hospitalizations in those with CKD due to T2DM.…”
Section: Clinical Evidencementioning
confidence: 99%